Avaliação do conhecimento sobre higiene bucal de pacientes atendidos em um curso de odontologia como precursor de mudanças de paradigmas de ensino - Assis, Larissa Oliveira de (2018)
The practice of health education aims to contribute to the care and promotion of health, providing health-disease control and the conduct of their habits through the insertion of knowledge. This study aims to compare the degree of knowledge about oral hygiene of individuais who are in integrated treatment in the integrated clinic of the Dental Course of UFES with individuais who are not performing dental treatment. Another objective is to use as a study model the person-centered care in the clinicai services of the Dentistry Course of the UFES beginning with changes in the clinicai routine in the teaching / leaming environment. This was a cross-sectional exploratory study of 174 patients who were divided into 87 patients who were in dental treatment and recruited 87 individuais who were in the waiting room following the patients attended but did not receive dental treatment. Regarding the profile of the sample, the female gender was predominant in both groups (71.26%). Regarding oral hygiene performed 3 times a day corresponded to 50.57% for the group being treated and 54.02% for the group of patients that were not being treated. Regarding dental loss issues for patients undergoing dental treatment, 93.10% presented and in the control group 80.46%, and approximately half of the sample of both groups did not know the reason for tooth loss. It can be concluded that it is evident that teaching did not present an emphasis on prevention, justifying the need to change the paradigm of teaching to a person-oriented model, and with this purpose it was proposed to implement a preventive protocol in the Dental Clinic education.